Role of the 3-mercaptopyruvate sulfurtransferase in colon/colorectal cancers - Matyasova, Katarina; Soltysova, Andrea; Babula, Petr; Krizanova, Olga; Liskova, Veronika (European journal of cell biology, 2024)
The 3-mercaptopyruvate sulfurtransferase (MPST) is a protein persulfidase, occurring mainly in mitochondria. Although function of this protein in cancer cells has been already studied, no clear outcome can be postulated up to now. Therefore, we focused on the determination of function of MPST in colon (HCT116 cells)/colorectal (DLD1 cells) cancers. In silico analysis revealed that in gastrointestinal cancers, MPST together with its binding partners can be either of a high risk or might have a protective effect. Silencing of MPST gene resulted in decreased ATP, while acetyl-CoA levels were elevated. Increased apoptosis was detected in cells with silenced MPST gene, which was accompanied by decrease in mitochondrial membrane potential, but no changes in IP3 receptor's protein. Mitochondria underwent activation of fission and elevated DRP1 expression after MPST silencing. Proliferation and migration of DLD1 and HCT116 cells were markedly affected, showing the importance of MPST protein in colon/colorectal cancer development.
Keywords: nádorové buněčné linie; Cell Movement; apoptóza; Sulfurtransferases; mitochondrie; kolorektální nádory; Dynamins; Colorectal Neoplasms; HCT116 buňky; Cell Proliferation; Cell Line, Tumor; HCT116 Cells; membránový potenciál mitochondrií; nádory tračníku; Humans; dynaminy; pohyb buněk; Colonic Neoplasms; sulfurtransferasy; proliferace buněk; Mitochondria; Membrane Potential, Mitochondrial; lidé; Apoptosis